Principles for the production of evidence‐based guidance for conservation actions. Issue 5 (28th April 2022) - Downey, Harriet; Bretagnolle, Vincent; Brick, Cameron; Bulman, Caroline R.; Cooke, Steven J.; Dean, Mike; Edmonds, Bob; Frick, Winifred F.; Friedman, Kim; McNicol, Catherine; Nichols, Christopher; Herbert, Saul; et al.
Abstract: Many types of guidance documents inform conservation by providing practical recommendations for the management of species and habitats. To ensure effective decisions are made, such guidance should be based upon relevant and up‐to‐date evidence. We reviewed conservation guidance for mitigation and management of species and habitats in the United Kingdom and Ireland, identifying 301 examples produced by over 50 organizations. Of these, only 29% provided a reference list, of which only 32% provided reference(s) relevant to justify the recommended actions (9% of the total). Furthermore, even this guidance was often outdated, lacked a methodology for production, or did not highlight uncertainty in the key evidence that supported the recommendations. These deficiencies can lead to misguided and ineffective conservation practices, policies, and decisions, and a waste of resources. Based on this review and co‐design by experts from 14 organizations, we present a set of principles for ensuring sufficient and relevant evidence is transparently incorporated into future conservation guidance. Producing evidence‐based guidance in line with these principles would enable more effective conservation outcomes.